O Livre acesso à informação científica em doenças negligenciadas: um estudo exploratório - Noronha, Ilma Maria Horsth (2011)
This paper discusses the access to scientific information on neglected diseases in the Fundação Oswaldo Cruz (Fiocruz), Brazil, in the light of the Open Access Movement. Although they account for nearly half of the disease burden in developing countries, neglected diseases research investments are admittedly bound and below of what are expected to lead to the necessary and urgent innovations in the public health sector. The free flow of scientific information is considered fundamental to burst health innovation. To guide this discussion, the theoretical framework goes back to pivotal role of communication in science, its social function and the recent changes in the sector of scientific publications that cause major changes in the way of publishing research results. The invisibility of scientific production from the developing countries is one of the main consequences, and the open access to scientific literature is a prime alternative. In order to discuss this issue in brazilian context, this dissertation asks key-actors of the Fiocruz which would be the major incentives and hindrances to the open access to scientific information. The results confirm the great potential of the movement of open access: authors attitudes to the open access movement are generally positive although some of them declare to know just `a little about this development. This is clearly calls for raising awareness of these issues in order to guide and contribute to the proposition of a public policy of open access to scientific information on health sciences